2015
DOI: 10.17323/1995-459x.2015.2.38.43
|View full text |Cite
|
Sign up to set email alerts
|

From Research Project to Research Portfolio: Meeting Scale and Complexity

Abstract: Keywordsresearch and development (R&D); peer review of R&D projects; project portfolio; portfolio-based approach; research performance evaluation From Research Project to Research Portfolio: Meeting Scale and ComplexityInvestment in research and innovation faces increasing scrutiny in countries that already do a lot of it. How much investment is optimal? How can we tell if and when our research activities offer less value for the dollar spent on them? How can we ensure that the benefits of investments accrue t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…As numerous observers have pointed out, interest in the evaluation of research activities and portfolios has been on the rise (e.g., Srivastava, Towery, and Zuckerman, 2007;Organisation for Economic Co-operation and Development [OECD], 2009;Wallace and Rafols, 2015;Linton and Vonortas, 2015). In a 2015 report, analysts from the United Kingdom (UK) Independent Review of the Role of Metrics in Research Assessment and Management observed, "there are powerful currents whipping up the metric tide" (Wilsdon et al, 2015, p. viii).…”
Section: Growing Interest Among Funders and Performers In Portfolio E...mentioning
confidence: 99%
See 1 more Smart Citation
“…As numerous observers have pointed out, interest in the evaluation of research activities and portfolios has been on the rise (e.g., Srivastava, Towery, and Zuckerman, 2007;Organisation for Economic Co-operation and Development [OECD], 2009;Wallace and Rafols, 2015;Linton and Vonortas, 2015). In a 2015 report, analysts from the United Kingdom (UK) Independent Review of the Role of Metrics in Research Assessment and Management observed, "there are powerful currents whipping up the metric tide" (Wilsdon et al, 2015, p. viii).…”
Section: Growing Interest Among Funders and Performers In Portfolio E...mentioning
confidence: 99%
“…Prospective impact assessments are limited and typically take the form of statements of envisaged impacts; those statements appear as part of funding applications (see, e.g., NSF, 2017). The more intentionally a portfolio is composed, the more easily it can be evaluated against the initial objectives (Linton and Vonortas, 2015). Discussions in this report focus on evaluating existing portfolios.…”
Section: Portfolio Evaluations Can Take Place At Multiple Stages Of T...mentioning
confidence: 99%
“…Иными словами, первичным становится целеполагание, а не сам выбор приоритетных направлений. Формальные аналитические инструменты и модели начинают использоваться только на уровне распорядителей бюджетов и экспертных комиссий [13].…”
Section: методологические подходыunclassified
“…Основу концепции управления проектами составляет взгляд на проект как на управлен-ческое изменение исходного состояния любой системы, связанное с затратами времени и средств Управление проектами включает функции планирования, организации, мониторинга и контроля по всем аспектам проекта для достижения его внешних и внутренних целей [13][14][15][16]. Задачами управления проектами являются:…”
Section: Ru/ Issn (Print) 2073-6185 Issn (On-line) 2542-095хunclassified